The effectiveness of leadership development in the military context from a gender viewpoint - Häyrynen, Heli; Lämsä, Anna-Maija (My University, 2021)
In this case study, leadership development is investigated from the viewpoint of women in a military context. In particular, the effectiveness of a leadership development program in a specific context, namely the Finnish Defence Forces, is explored. The program being studied is unique because it is concerned with developing volunteers, not professional soldiers. A longitudinal, interview-based study of the topic was conducted with women who had participated in the program. The data consists of 45 open-ended interviews with 15 women. Each woman was interviewed three times: at the beginning, in the middle and at the end of the program. Content analysis was used to analyse the data. The results show that the current leadership model for effective leadership in the Finnish Defence Forces would benefit especially from the addition of an intrapersonal leadership competence dimension, to better take women's needs into consideration. By making the female point of view visible and acknowledging women's views, new resources can be created for military organisations.
Keywords: case study; effectiveness; leadership development; woman; gender; military leadership